Silica Coating of Ferromagnetic Iron Oxide Magnetic Nanoparticles Significantly Enhances Their Hyperthermia Performances for Efficiently Inducing Cancer Cells Death In Vitro - Cristian Iacoviță; Ionel Fizeșan; Stefan Nitica; Adrian Florea; Lucian Barbu-Tudoran; Roxana Dudric; Anca Pop; Nicoleta Vedeanu; Ovidiu Crisan; Romulus Tetean; Felicia Loghin; Constantin Mihai Lucaciu (Pharmaceutics, 2021)
Increasing the biocompatibility, cellular uptake, and magnetic heating performance of ferromagnetic iron-oxide magnetic nanoparticles (F-MNPs) is clearly required to efficiently induce apoptosis of cancer cells by magnetic hyperthermia (MH). Thus, F-MNPs were coated with silica layers of different thicknesses via a reverse microemulsion method, and their morphological, structural, and magnetic properties were evaluated by multiple techniques. The presence of a SiO2 layer significantly increased the colloidal stability of F-MNPs, which also enhanced their heating performance in water with almost 1000 W/gFe as compared to bare F-MNPs. The silica-coated F-MNPs exhibited biocompatibility of up to 250 μg/cm2 as assessed by Alamar Blues and Neutral Red assays on two cancer cell lines and one normal cell line. The cancer cells were found to internalize a higher quantity of silica-coated F-MNPs, in large endosomes, dispersed in the cytoplasm or inside lysosomes, and hence were more sensitive to in vitro MH treatment compared to the normal ones. Cellular death of more than 50% of the malignant cells was reached starting at a dose of 31.25 μg/cm2 and an amplitude of alternating magnetic field of 30 kA/m at 355 kHz.